2008
DOI: 10.1002/pssa.200777453
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent site change of In in AlN and GaN

Abstract: Hyperfine interaction studies by means of the perturbed angular correlation technique have been carried out on In implanted into GaN and AlN. After the implantation of the probe 111In with 160 keV and annealing of the radiation damage for 120 s at 1273 K, it is found, that in both materials 50–60% of the In probes occupy regular lattice sites at room temperature. The remaining second fraction is found in a quite different but relatively well defined lattice environment. The regular fraction increases at the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Recent PAC-studies of 111 In-implanted GaN indicated that after annealing In forms a complex with an unidentified defect that is strongly dependent on the temperature at which the measurement is performed [3]. An equivalent behaviour was also reported for 111 In implanted AlN [4,5]. Here we present temperature dependent PAC studies with the probe 181 Hf implanted into GaN.…”
Section: Introductionmentioning
confidence: 67%
“…Recent PAC-studies of 111 In-implanted GaN indicated that after annealing In forms a complex with an unidentified defect that is strongly dependent on the temperature at which the measurement is performed [3]. An equivalent behaviour was also reported for 111 In implanted AlN [4,5]. Here we present temperature dependent PAC studies with the probe 181 Hf implanted into GaN.…”
Section: Introductionmentioning
confidence: 67%
“…In-V N was also observed in AlInN where the characteristic signal is even more pronounced than in GaInN [5]. In-V N could be a competing exciton trap and may be involved in the processes leading to the high efficacy.…”
Section: Introductionmentioning
confidence: 91%
“…In previous measurements [3][4][5] it was shown, that in addition to indium on substitutional cation (Ga/Al) sites a configuration attributed to an indium nitrogenvacancy (…”
Section: Introductionmentioning
confidence: 99%
“…In previous measurements [3][4][5] it was shown, that in addition to indium on substitutional cation (Ga/Al) sites a configuration attributed to an indium nitrogenvacancy (V N ) defect complex (In-V N ) is observed with the PAC probe 111 In. The electric field gradient (EFG) of the In-V N is oriented parallel to the c-axis of the crystal.…”
Section: Introductionmentioning
confidence: 98%